Analytical model of the network topology and rigidity of calcium aluminosilicate glasses. Issue 8 (21st April 2021) - Yang, Kai; Hu, Yushu; Li, Zhou; Krishnan, N. M. Anoop; Smedskjaer, Morten M.; Hoover, Christian G.; Mauro, John C.; Sant, Gaurav; Bauchy, Mathieu
Abstract: Topological constraint theory (TCT) has enabled the prediction of various properties of oxide glasses as a function of their composition and structure. However, the robust application of TCT relies on accurate knowledge of the network structure and topology. Here, based on classical molecular dynamics simulations, we derive a fully analytical model describing the topology of the calcium aluminosilicate [(CaO) x (Al2 O3 ) y (SiO2 )1− x − y, CAS] ternary system. This model yields the state of rigidity (flexible, isostatic, or stressed‐rigid) of CAS systems as a function of composition and temperature. These results reveal the existence of correlations between network topology and glass‐forming ability. This study suggests that glass‐forming ability is encoded in the network topology of the liquid state rather than that of the glassy state.